Multi-temporal Analysis for Differential Interferometry Synthetic Aperture Radar (D-InSAR) and Its Application to Monitoring Land Surface Displcements - Yastika, Putu Edi; Shimizu, Norikazu; Tanaka, Tasuku; Osawa, Takahiro (International Journal of Environment and Geosciences; Vol 1 No 1 (2017), 2017)
Land subsidence rate in Semarang has been observed by D-InSAR technique based on ALOS-PALSAR data on ascending orbits, which is processed by GMTSAR and ArcGIS software. Two kind of methods namely single D-InSAR and Multi-Temporal D-InSAR has been done. By employing SRTM3 and ASTER1 DEM data to remove the topography component, total 67 pairs of inteferogram has generated. Northeast area and shoreline area has largest subsidence about 20-32 cm for 4 years or average rate 5-8 cm/year. Since the northwest area and center area has lower subsidence rate and even no remarkable subsidence occurred, this area seems to be stable comparing the northeast area. Removing the topography component phase to get displacement phase from the phase interferogram by using SRTM3 DEM and ASTER1 DEM data respectively, the both results coincided with 0.995 correlation value. The coherence threshold is an important factor to get better accuracy, but if setting the threshold too high, the process of interference will be failed and not be able to obtain the results in a lot of area. The perpendicular baseline and the temporal baseline (time period) is an important factor to determining the coherence threshold. By using many scenes the Multi-Temporal D-InSAR was applied, and by selecting good pairs of the interferograms, accuracy of the results will be improved. The correlation value for GPS data eventually increased from 0.63 to 0.77.
Keywords: ALOS-PALSAR; D-InSAR; GPS; hyperbolic method; land subsidence; multi-temporal method